2012
DOI: 10.1002/jobm.201100290
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Anticancer activity of ε ‐poly‐L‐lysine (ε ‐PL) produced by a marine Bacillus subtilis sp.

Abstract: A marine Bacillus subtilis SDNS was isolated from sea water in Alexandria and identified using 16S rDNA sequence analysis. The bacterium produced a compound active against a number of gram negativeve bacteria. Moreover, the anticancer activity of this bacterium was tested against three different human cell lines (Hela S3, HepG2 and CaCo). The highest inhibition activity was recorded against Hela S3 cell line (77.2%), while almost no activity was recorded towards CaCo cell line. HPLC and TLC analyses supported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(43 citation statements)
references
References 28 publications
0
42
0
1
Order By: Relevance
“…Pokrovsky reported that L-Lysine α-oxidase showed considerable cytotoxicity against seven tumor cell lines [28]. El-Sersy also isolated a poly-lysine component which inhibited three human cell lines (Hela S3, HepG2 and CaCo) [29]. Our investigation demonstrated that J2-C3 had a higher level of lysine, which might be related to the anti-tumor activity, but its mechanism needs to be studied further.…”
Section: Discussionmentioning
confidence: 64%
“…Pokrovsky reported that L-Lysine α-oxidase showed considerable cytotoxicity against seven tumor cell lines [28]. El-Sersy also isolated a poly-lysine component which inhibited three human cell lines (Hela S3, HepG2 and CaCo) [29]. Our investigation demonstrated that J2-C3 had a higher level of lysine, which might be related to the anti-tumor activity, but its mechanism needs to be studied further.…”
Section: Discussionmentioning
confidence: 64%
“…Fractions of viable cells were measured with MTT assay. [33] The inhibition of growth rate of tumour cells for each compound with different concentrations was calculated as follows: [100 ¡ (absorbance of cells that were exposed to the compound at different concentrations/absorbance of control well)] £ 100.…”
Section: ¡1mentioning
confidence: 99%
“…Anticancer ε -poly-L-lysine (ε -PL) was produced by a marine Bacillus subtilis sp. isolated from sea water in Alexandria [26]. We isolated a strain, S-1, from the bottom sediments of South China Sea.…”
Section: Resultsmentioning
confidence: 99%